Impact of Number of Phases on Electromagnetic Torque Characteristics of Transverse Flux Permanent Magnet Machines - Alaeddini, A.; Tahanian, H.; Darabi, A. (Advanced Electromagnetics, 2019)
This paper presents an investigation on the influences of number of phases of Transverse Flux Permanent Magnet (TFPM) machines on the characteristics of developed electromagnetic torque. Electromagnetic torque is expressed in terms of the Fourier series of phase currents and internal voltages. After some algebraic and trigonometric calculations, a general equation is obtained that establishes a relationship between the electromagnetic torque ripples, number of phases and harmonic contents of both internal voltages and phase currents. This result is significant when it is required to design a few specific number of identical single-phase TFPM machines which finally they will be assembled such that to build a multi-phase machine with a minimum torque ripple. The design parameters of a case study Claw Pole TFPM machine are introduced with some details and a few FE based simulation results are given as the validations of the analytical approach of the present paper. The simulation results show clearly the impact of each harmonic of the internal voltages and phase currents on the torque ripple for various numbers of phases leading the designer to find out which number of single-phase machine combinations is the optimum one regarding the torque ripple.